توظيف القواعد التحويلية عند نعوم تشومسكي في استيعاب المجاز المرسل: دارسة على نماذج من الآيا ت القرآنية - Ajwad Mohd Zulqurnain; Ahmad Lutfi Zakaria; Aisyah Aminah Che Amran; Siti Aishah Bakri; Wan Najihah Wan Saidi; Mohd Ikhwan Abdullah (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia